An integrated pelagic carbonate multi-proxy study using portable X-ray fluorescence (pXRF): Maastrichtian strata from the Bottaccione Gorge, Gubbio, Italy. (November 2018) - Sinnesael, Matthias; de Winter, Niels J.; Snoeck, Christophe; Montanari, Alessandro; Claeys, Philippe
Abstract: Pelagic carbonate sections constitute common archives for paleoclimatological and stratigraphical research. This study evaluates the use of portable X-ray fluorescence (pXRF) measurements on pelagic carbonates and applies the method to the well-studied latest Maastrichtian in the Bottaccione Gorge section from Gubbio, Italy. A calibration with carbonate reference materials makes it possible to acquire absolute elemental concentrations, and allows for comparison with results from previous geochemical studies, which used more expensive and time consuming conventional techniques, such as neutron activation or Inductively Coupled Plasma Mass Spectrometry (ICP-MS). With adequate measurement strategies and careful calibration, pXRF measurements can be a reliable, non-destructive, cheap, fast and easy to use alternative to acquire multi-elemental concentration data (Ca, Fe, Mn, Sr) in pelagic carbonates. These pXRF elemental concentration data represent valuable additions to classical proxies such as magnetic susceptibility and calcium carbonate content used in the study of pelagic carbonates. Furthermore, the potential of the portable pXRF method for applications in cyclostratigraphical (e.g. using Fe-concentrations) and chemostratigraphical (e.g. using Mn and Sr concentrations) investigations is demonstrated. A strong covariation between the measured Sr concentration profile obtained by pXRF and the existing δ 18 O record, in combination with micro-XRF mapping, demonstrated the sampling of calcite veins in some of the samples. The first 87 Sr/ 86 Sr isotope measurements for the latest Maastrichtian in the Bottaccione Gorge section seem to be little affected by this sampling effect.